2019
DOI: 10.1038/s41598-019-56577-7
|View full text |Cite
|
Sign up to set email alerts
|

Distinct pathways for zinc metabolism in the terrestrial slug Arion vulgaris

Abstract: In most organisms, the concentration of free Zn2+ is controlled by metallothioneins (MTs). In contrast, no significant proportions of Zn2+ are bound to MTs in the slug, Arion vulgaris. Instead, this species possesses cytoplasmic low-molecular-weight Zn2+ (LMW Zn) binding compound that divert these metal ions into pathways uncoupled from MT metabolism. Zn2+ is accumulated in the midgut gland calcium cells of Arion vulgaris, where they associate with a low-molecular-weight ligand with an apparent molecular mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Here, we assembled and annotated a chromosome-level genome of A. vulgaris, which could provide crucial resources to infer its evolutionary history, elucidate its distribution pattern and explore genetic mechanisms that might be related to its quick adaption and invasiveness. This genetic resource can be fundamental for several lines of applied research, such as for exploring mucus related genes and pathways for medical research [24]. Moreover, the genome is the first land slug genome published to date: by comparison with land snails, it will be a good reference for exploring the evolution of shell losses in Stylommatophora, and potential substitutes of the shell functions, such as chemical weapons or an enhanced immune system in land slugs.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we assembled and annotated a chromosome-level genome of A. vulgaris, which could provide crucial resources to infer its evolutionary history, elucidate its distribution pattern and explore genetic mechanisms that might be related to its quick adaption and invasiveness. This genetic resource can be fundamental for several lines of applied research, such as for exploring mucus related genes and pathways for medical research [24]. Moreover, the genome is the first land slug genome published to date: by comparison with land snails, it will be a good reference for exploring the evolution of shell losses in Stylommatophora, and potential substitutes of the shell functions, such as chemical weapons or an enhanced immune system in land slugs.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] . Its composition may vary across species and based on its function 30,31 , but generally comprises of over 90% water and a variety of proteoglycans, glycosaminoglycans, glycoprotein enzymes, hyaluronic acid, copper peptides, antimicrobial, antifungal, and antiviral peptides 31,32 , and metal ions [33][34][35] . Slugs lacking the protective shell of snails are known to secrete an extremely stiff mucus when endangered or disturbed by predators or humans [36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…Arionid slugs are reported fairly tolerant to heavy metals which they tend to accumulate in high concentrations in their midgut gland. However, excessive concentrations of zinc, lead, and copper are toxic and can negatively impact the slug's metabolism of other essential metal ions [29]. It has been reported that heavy metals could be used in slug control programs as an antifeedant and so-called bioactive repellents [30], but there is still inconsistency in efficiency since the toxicity of Zn, Pb or other heavy metals is dosage-dependent [31].…”
Section: Discussionmentioning
confidence: 99%